2013
DOI: 10.1097/00003643-201306001-00565
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive mechanical ventilation after the successful weaning: a comparison with the venturi mask

Abstract: Background and objectives: This study compared the rates of acute respiratory failure, reintubation, length of intensive care stay and mortality in patients in whom the non-invasive mechanical ventilation (NIMV) was applied instead of the routine venturi face mask (VM) application after a successful weaning. Methods: Following the approval of the hospital ethics committee, 62 patients who were under mechanical ventilation for at least 48 hours were scheduled for this study. 12 patients were excluded because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…After excluding 334 duplicates and 3134 irrelevant citations, we reviewed the full text of the remaining 62 records. Finally, a total of 17 eligible RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], representing 3341 patients, were included in this NMA. The PRISMA flowchart for study inclusion is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding 334 duplicates and 3134 irrelevant citations, we reviewed the full text of the remaining 62 records. Finally, a total of 17 eligible RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], representing 3341 patients, were included in this NMA. The PRISMA flowchart for study inclusion is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 17 included RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], 10 [23, 26-28, 38, 41, 43-46] were multicenter, and 7 [37,39,40,42,[47][48][49] were single-center. All included RCTs were published in the last 15 years, and the number of participants ranged from 38 to 614.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations